Does Intellectual Capital Matter? A Case Study of Indonesia Sharia Banks - Dian Kartika Rahajeng; Nadya Zahara Hasibuan (The Indonesian Journal of Accounting Research, 2020)
This study aim is to examine the impact of Intelectual Capital (IC) on financial performance in the Islamic banking sector in Indonesia. We adopt the Pulic’s value-added intellectual coefficient (VAIC™) as the widely used measurement for IC. The paper used secondary data derived from the annual reports of eleven Islamic banks from 2012 to 2016. This study uses firm size and level of risk as a control variable. We utilise the resource dependency theory as an analytical tool. The findings show that the IC does not significantly matter and influence the profitability of Islamic banks. However, the results also show a significant impact on human capital and structural capital on profitability of sharia bank. The findings can be useful as an input for the practitioners in Islamic banks in managing their investments in IC in Indonesia Islamic banks. This paper also contributes to the theory and literature by particularly the adoption of resource dependency theory to analyse the IC in Islamic banks.